Exploring the Essence, Importance, and Distinctive Attributes of Islamic Culture: An In-depth Cultural Analysis - Mahmudulhassan Mahmudulhassan (Bulletin of Islamic Research, 2024)
Islamic culture is a testament to the rich tapestry of human civilization, interwoven with history, religion, philosophy, and art. This paper embarks on a comprehensive exploration of Islamic culture's essence, importance, and distinctive attributes through an in-depth cultural analysis. Drawing upon a qualitative research methodology, the study focuses on the historical development, religious foundations, artistic expressions, and societal norms within Islamic civilization. By synthesizing data from academic literature, primary sources, and expert interviews, the paper provides a nuanced understanding of Islam's historical and cultural dimensions, particularly in society. The research methodology employed involves a systematic review of relevant literature and primary documents, supplemented by interviews with experts in Islamic culture. The study emphasizes the importance of Islamic culture, not only for Muslims but also for humanity as a whole, serving as a source of spiritual guidance, moral framework, and cultural identity. Furthermore, the paper examines the salient characteristics of Islamic culture, including its emphasis on monotheism, diversity, social cohesion, and intellectual legacy. It underscores the significance of Islamic culture in fostering cross-cultural dialogue, promoting mutual respect, and shaping global perspectives. In conclusion, the study advocates for a deeper appreciation and understanding of Islamic culture's enduring legacy, calling for efforts to promote peace, justice, and understanding in our diverse and interconnected world.